Why Do Entrepreneurially Trained Graduates Choose Employment? A Phenomenological Inquiry in Aceh Higher Education - Hendra Halim; Meutia Dwi Novita Sari; Khoirul Amri (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2025)
This phenomenological study investigates why entrepreneurially trained graduates choose employment rather than founding ventures in the Aceh higher-education context. Using Interpretative Phenomenological Analysis (IPA), we conducted semi-structured interviews with 12 alumni who completed entrepreneurship courses/competitions/incubation yet currently work as employees. Analysis generated five superordinate themes: (1) temporary competitive euphoria—competitions boost confidence, networks, and credentials but fade without aftercare; (2) stability rationality and risk aversion—employment is framed as pragmatic adaptation to income needs, market uncertainty, and family obligations; (3) campus-to-market ecosystem gaps—a “missing middle” between pitch events and real operations (financing, compliance, distribution); (4) hybrid career identity and skill transfer—entrepreneurial skills persist via intrapreneurship and low-risk side projects; and (5) temporal opportunity and momentum loss—post-graduation delays narrow windows and disperse teams. We conclude that employment is not an antithesis to entrepreneurship but a meaningful, risk-managing pathway within constrained ecosystems. Practical implications include building a curriculum-to-venture pipeline, staged evidence-gated funding, 6–12-month transition fellowships, one-door compliance/production clinics, anchor-demand partnerships, and formal intrapreneurship tracks. The study reframes the intention–behavior gap as employment-oriented adaptation and suggests longitudinal, multi-site research to test and refine this pathway.